Sistem Informasi Penghitungan Pembayaran Kuliner Pada CafÃ© Aira Rantauprapat - Pohan, Cita; Nasution, Fitri Aini (Universitas Labuhanbatu, 2021)
The development of technology is currently developing very rapidly. and bring a very big change because with technology we can get information, access information quickly. With the development of today we can use computers as a tool to facilitate human work, thereby reducing the risk of errors, in order to be more effective, safe, fast, and accurate.Cafe is a place to relax and chat where visitors can order drinks and food. In general, restaurants or cafes have difficulty calculating the list of food menus and prices to be paid visitors, the difficulty is because the calculation is done by the admin is still manually, often errors in calculations that cause losses in the cafe. This study aims to make cafe operations can run more effectively, safely, quickly, and accurately. With this information system, the admin can control or process the process of payment data in the cafe because it has been computerized, so that the data can be stored properly .